Urine Soluble CD163 Is a Promising Biomarker for the Diagnosis and Evaluation of Lupus Nephritis - Huang, Yun-Ju; Lin, Chiung-Hung; Yang, Huang-Yu; Luo, Shue-Fen; Kuo, Chang-Fu (Frontiers in Immunology, 2022)
Introduction Urine soluble CD163 (usCD163) is released from alternatively activated macrophages involved in the resolution of inflammation in glomeruli, and plays an important role in glomerulonephritis. This study explored the role of usCD163 in patients with systemic lupus erythematosus (SLE). Materials and Methods usCD163 concentrations were measured cross-sectionally in 261 SLE patients in Taiwan. Clinical and laboratory data were collected, and SLE disease activity scores were calculated to assess the correlation with usCD163. Results SLE patients with high usCD163 levels tended to be younger, with a higher hospital admission rate, higher prednisolone dose, lower estimated glomerular filtration rate, higher urine protein creatinine ratio (UPCR), more pyuria and hematuria, higher levels of inflammatory markers, higher rates of anemia, neutropenia, and lymphopenia, lower complement 3 (C3) levels, higher anti-double stranded DNA antibody (anti-dsDNA Ab) levels, and higher disease activity scores (p < 0.05). usCD163 levels were significantly higher in patients with active lupus nephritis (LN) than in those with extrarenal or inactive SLE, and correlated with UPCR, disease activity, and anti-dsDNA Ab levels. SLE patients with high usCD163 levels tended to have a higher chronic kidney disease stage. Discussion and Conclusion The usCD163 level correlates with the severity of LN and disease activity in renal SLE.